Patrimônio e memória : o Theatro Sete de Setembro na construção da identidade Penedense (1884-1950) - Santos, Gustavo Pereira (2023)
This work is dedicated to investigating the construction of the collective identity of Penedo-AL through Theatro Sete de Setembro between 1884, the year of its foundation, and 1950. Penedo during the 19th century had a large area of economic influence in the Lower São Francisco, which led to the construction of the theater through the Imperial Philharmonic Society Sete de Setembro. During the end of the Empire and the beginning of the Republic, the city developed and managed to consolidate itself as one of the main cities in the region, mainly with the participation of the river port. We seek to understand, in this way, how Theatro Sete de Setembro participated in Penedense society at a time of economic and social effervescence in the Baixo São Francisco region, as well as which groups would be its regulars, in the construction of the collective identity of the city. We observe the context of the city of Penedo in the 19th century, discussing the role of the theater maintainer in its construction and, then, the construction of the theater itself, the elements of neoclassical architecture and how they are present in the external and internal structure. The guiding concepts of the research focus on collective memory and identity. Finally, newspapers from the period that served as a source, the discussion takes place around the events that took place in the theater during the period, either through ceremonies of the owner association, or through artistic presentations or use of the theater as a cinema. At the end, we will make a brief final consideration about the role of theater in the city of Penedo during these 70 years analyzed.